On macroeconomic determinants of co-movements among international stock markets: evidence from DCC-MIDAS approach - Gungor, Arifenur; Tastan, Huseyin (AMER INST MATHEMATICAL SCIENCES-AIMS, 2021)
This study aims to examine the macro-financial dynamics of the time-varying co-movements between the daily stock market returns of G7 and BRICS-T countries using a two-step procedure. Firstly, we decompose the dynamic conditional correlations between the daily stock market returns into the short-term (daily) and the long-term (quarterly) components using the DCC-MIDAS (Dynamic Conditional Correlation-Mixed Data Sampling) method for the period from 2002 to 2018. Then, we estimate the relationship between the quarterly DCC-MIDAS correlations and quarterly macroeconomic variables that represent the economic-financial proximity between country pairs using the System GMM (Generalized Method of Moments) method. Empirical results suggest that the most important factors which explain the long-term dynamic conditional correlations between the stock market returns of G7 and BRICS-T countries are the differences in GDP growth rates, five-year CDS risk premiums, and EPU (Economy Policy Uncertainty) indices between the country pairs.
Keywords: stock markets; time-varying co-movements; macroeconomics; DCC-MIDAS; VOLATILITY SPILLOVERS; FINANCIAL CRISIS; CONTAGION; DEPENDENCE; Business & Economics